2014
DOI: 10.4149/av_2014_02_194
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a goose parvovirus from swan and its molecular characteristics

Abstract: Summary. -Goose parvovirus (GPV) causes high mortality and morbidity in goslings and Muscovy ducklings. In this study, a GPV was isolated from a 20-day old swan in Shanghai, China. Complete genome of the swan isolate contained 5,050 nt and showed the highest homology with Taiwanese GPV isolates from 1982. In comparison with the Chinese mainland GPV isolates reported previously, the swan isolate shows two deletions, particularly at positions 67-80 and 334-347 in inverted terminal repeats (ITRs). These findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Normally, GPVs have been found in goslings, Muscovy ducklings [5, 8], swans [9], and Anser cygnoides [10], whereas MDPV has only been discovered in Muscovy ducklings. MDPV infection was initially described by Professor Lin in our laboratory in the early 1980s [11].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, GPVs have been found in goslings, Muscovy ducklings [5, 8], swans [9], and Anser cygnoides [10], whereas MDPV has only been discovered in Muscovy ducklings. MDPV infection was initially described by Professor Lin in our laboratory in the early 1980s [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous observation and research indicated that the goose parvovirus can infect both goslings and ducklings. Then, goose parvovirus was isolated from swans in China in 2012 [9] . Earlier studies have confirmed that goose parvovirus genome remained genetically stable in the field.…”
Section: Discussionmentioning
confidence: 99%
“…8,[18][19][20] This consistency in genome length is similar to the genomes of other parvoviruses, which also package single-stranded DNA into an icosahedral capsid of similar size. [21][22][23][24] This suggests that the maximum packaging capacity of members of the Parvoviridae family is approximately 4.5-5.5 kb.…”
Section: Packaging Capacity Of Viruses Of the Parvoviridae Familymentioning
confidence: 99%